Extracellular lipid-free apolipoprotein E inhibits HCV replication and induces ABCG1-dependent cholesterol efflux. Issue 5 (8th September 2016) - Crouchet, Emilie; Lefèvre, Mathieu; Verrier, Eloi R; Oudot, Marine A; Baumert, Thomas F; Schuster, Catherine
Abstract : Objective: The HCV life cycle and the lipid metabolism are inextricably intertwined. In the blood, HCV virions are associated with lipoproteins, forming lipoviroparticles (LVPs), which are the most infectious form of the virus. Apolipoprotein E (apoE), a key LVP component, plays an essential role in HCV entry, assembly and egress. ApoE is also a cell host factor involved in lipoprotein homeostasis. Although the majority of apoE is associated with lipoproteins, a lipid-free (LF) form exists in blood. However, the role of LF-apoE in both lipid metabolism and HCV life cycle is poorly understood. Design: In this study, using the cell culture-derived HCV model system in human hepatoma Huh7.5.1 cells and primary human hepatocytes (PHH), we investigated the effect of LF-apoE on the early steps of HCV life cycle and on the lipid metabolism of hepatic cells. Results: A dose-dependent decrease in HCV replication was observed when Huh7.5.1 cells and PHH were treated with increasing amounts of LF-apoE. We showed that LF-apoE acts on HCV replication independently of previously described apoE receptors. We observed that LF-apoE induced a marked hepatic cholesterol efflux via the ATP-binding cassette subfamily G member 1 (ABCG1) protein that in turn inhibits HCV replication. LF-apoE also increases both apolipoprotein AI and high-density lipoprotein production. Conclusions: Our findings highlight a new mechanism in lipid metabolism regulation and interaction of the lipid metabolism with the HCV life cycle, which may be important for viral pathogenesis and might also be explored for antiviral therapy.